Development of structural-parametric optimization method in systems with continuous feeding of technological products - Lutsenko, Igor; Koval, Svetlana; Oksanych, Iryna; Serdiuk, Olga; Kolomits, Hanna (Eastern-European Journal of Enterprise Technologies, 2018)
Increasing the efficiency of continuous technological processes, in practice, involves certain difficulties. The presence of these difficulties is due to the fact that the technological product quality is functionally related to energy consumption. In turn, the lack of necessary degrees of freedom, within the framework of the system under investigation, limits the optimization capabilities of control processes. To increase the degrees of freedom of control, the technological mechanism was divided into technological sections. The sections allow collecting independent modules, each of which has its own subsystem of stabilization of the technological product qualitative parameter. This approach allowed us to set different trajectories of changes in the technological product qualitative parameters within one production stage. As a result of the research, it was found that the change in the technological mechanism structure (the modules number) and the trajectory of the change in the technological product qualitative parameter made it possible to change the total energy consumption and wear of the working mechanisms of equipment. The proposed approach made possible to obtain two degrees of freedom of control: the possibility of changing the sectional structure into self-stabilizing modular systems and changing the trajectory of the technological product qualitative parameter within the production stage. The obtaining of degrees of freedom of control, in turn, allowed to change the resource efficiency of the continuous technological process and to develop the method of structural-parametric optimization. As an optimization criterion, an evaluation indicator was used, which was verified for the possibility to use it as an efficiency criterion. As a result, the optimization control capabilities are significantly increased. The principles of the approach are considered in the work with the example of one-, two- and three-step process of continuous liquid heating.